2013
DOI: 10.1074/jbc.m112.403832
|View full text |Cite
|
Sign up to set email alerts
|

ISG15 Deregulates Autophagy in Genotoxin-treated Ataxia Telangiectasia Cells

Abstract: Background: Aberrant activation of autophagy (proteinopathy) leads to neurodegeneration in various neurological disorders. Results: Compensatory basal autophagy is activated, and genotoxins deregulate autophagy in the ubiquitin pathway-compromised ataxia telangiectasia (A-T) cells. Conclusion: Deregulation of autophagy is due to the elevated expression of ISG15 in A-T cells. Significance: Results highlight a causal contribution of a novel "ISG15 proteinopathy" in A-T neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Lysosomal and bacterial staining were performed as previously described [44], [45]. Briefly, RAW cells were treated with 50 nM LysoTracker-Red DND-99 (Life Technology) with and without MMR blocking with 4 mg/ml mannan (Sigma) or 0.5 µg/ml anti-MMR/CD206 pAb (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…Lysosomal and bacterial staining were performed as previously described [44], [45]. Briefly, RAW cells were treated with 50 nM LysoTracker-Red DND-99 (Life Technology) with and without MMR blocking with 4 mg/ml mannan (Sigma) or 0.5 µg/ml anti-MMR/CD206 pAb (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…25 Recently, Desai et al revealed that high ATG7 expression level is associated with poor patient survival in breast cancer. 26 Similar important roles of ATGs have also been demonstrated in the development of other cancers. 27,28 Together, these findings indicate that autophagy plays an important role in carcinogenesis.…”
Section: Introductionmentioning
confidence: 59%
“…In addition to blocking polyubiquitin chains formation, protein ISGylation can regulate the UPS system by other means such as competition for E1/E2/E3s ubiquitylation enzymes 50 and for substrate lysines 49 . In combination, these different arms convey a general inhibitory effect on UPS function, which may lead to multiple downstream effects, including the activation of the autophagy pathway 61 , the formation of cellular inclusions 51 , and inflammatory cytokine production (Fan et al . manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%